Mechanisms of High Concentration Valine-Mediated Inhibition of Peach Tree Shoot Growth - Li, Suhong; Peng, Futian; Xiao, Yuansong; Gong, Qingtao; Bao, Ziyi; Li, Yanyan; Wu, Xuelian (Frontiers in Plant Science, 2020)
The vigorous growth of the new shoots of the peach tree was not beneficial to high quality and efficient cultivation. High concentration of amino acids can inhibit plant growth, but the mechanism is not clear. In this study, we explored the regulatory effects of seven amino acids (phenylalanine, valine, leucine, isoleucine, serine, D-alanine, proline) (10 g·L−1) on the growth of peach trees. The results showed that phenylalanine, valine, and proline inhibited peach seedling growth and valine has the most significant effect and it can promote the root growth of peach seedlings. Compared with paclobutrazol, valine treatment improves net photosynthetic rate and fruit quality without reducing shoot diameter or puncture strength, and it does not affect leaf morphology. Valine enhanced the expression of PpSnRK1 (sucrose non-fermenting-1-related protein kinase) and inhibited the expression of PpTOR (Target of Rapamycin) and PpS6K (Ribosomal S6 kinase). The gibberellin content was significantly reduced in the valine treatment group. The endogenous valine content of peach seedlings was increased, acetohydroxyacid synthase (AHAS, E.C. 2.2.1.6) activity was inhibited by feedback, isoleucine synthesis was decreased, the relative amounts of branched chain amino acids were unbalanced, and growth was inhibited. However, isoleucine spraying after valine treatment could increase the content of isoleucine and alleviate the inhibition of valine on the shoot growth. In conclusion, valine is environmentally friendly to inhibit the growth of new shoots of peach trees by regulating the balance of PpSnRK1 and PpTOR and the synthesis of isoleucine.